Association between serum midkine levels and tumor size in Indonesian hepatocellular carcinoma patients: a cross-sectional study - Darmadi Darmadi; Ruslie Riska Habriel; Pakpahan Cennikon (Sciendo, 2022)
Background: The incidence of liver cancer is increased worldwide with 75%-85% diagnosed as hepatocellular carcinoma (HCC). Current practice has low sensitivity limitations to diagnose the early stages of HCC, thus urging the need for a biomarker with higher sensitivity to detect HCC, specifically in the early stage. This study aimed to determine the association between midkine levels and progressiveness of hepatocellular carcinoma (HCC), according to tumor size, Barcelona Clinic Liver Cancer (BCLC), and presence of portal venous thrombosis.